Influence of TiO2 and ZrO2 nanoparticles deposition on a stainless steel furnace used for trace element determination by TS-FF-AAS - Carrone, Guillermo Alejandro (2019)
In this study, we presented the influence of nanoparticle coatings over the inner furnace wall used in TS-FF-AAS for the determination of trace elements (Ag, Cd, Pb, and Se) in different complex matrix. The use of ceramic nanomaterials (ZrO2 and TiO2) as a coating, produced by the dipcoating technique, enabled enhanced analytical performance (analytical response, sensitivity, LOD, LOQ, and signal stability). This furnace modification was used for determining the analytes in different samples.